Study of environment based condition of electromagnetic interference during ECG acquisition - W., Y. Wong; Rubita, Sudirman; Nasrul Humaimi, Mahmood, Dr.; Siti Zubaidah, Mohd Tumari; N., Samad (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/